What is the difference in TOS progression secondary to complete vs. incomplete cervical ribs? - Ammara Bint I Bilal (14777176) (2023)
When complete cervical ribs are present, clinicians and surgeons should look out for the possibility of arterial involvement with disease progression similar to what happened in this case. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4311